Functionalisation through periodically arranged nanostructures. (7th February 2012) - Sahaf, Houda; Moyen, Eric; Macé, Magali; Masson, Laurence; Hanbücken, Margrit; Gerhard, Lukas; Wulfhekel, Wulf
The controlled fabrication of uniform nanostructure arrays and their subsequent use for selective functionalisations of substrates is of increasing interest for controlled applications in nanotechnology. Fabrication of nanostructures via epitaxial growth has turned out to be an interesting alternative to standard lithography methods. In this work, we present the elaboration and fabrication of ordered, regular arrays of identical nanostructures, arranged in either one or two dimensions, obtained through different experimental bottom–up and top–down approaches. These nanostructures can be grown in different sizes and various shapes like nanoparticles, nanodiscs or nanostripes. One–dimensional nanostructure arrangements are obtained through the controlled growth on previously nanopatterned templates like vicinal Si(111) substrates or structured Ag(110) surfaces. Two–dimensional nanostructure arrangements are obtained by deposition of the adsorbate material through the openings of a nanoporous alumina membrane, serving in this case as an evaporation mask. A local functionalisation of substrates can be obtained in specific cases like growth of magnetic material on silicon or catalytic matter and graphene on silicon carbide and will be described.